'It's All About Justice': Bodies, Balancing Competing Interests, and Suspicious Deaths. (8th November 2018) - Jones, Imogen
Abstract : This article draws upon a series of interviews with Home Office Registered Forensic Pathologists to understand how they view and balance competing interests in a deceased body. The actions and professional ethos of this small group of doctors who carry out autopsies in suspicious death cases have very real consequences for both the living and dead. We need to understand the decisions that are being made about our bodies and the remains of those who matter to us, what motivates these and whether they stand up to scrutiny. It is argued that retributive justice both inspires the pathologists and justifies the distress that investigations of suspicious death can cause the bereaved. This approach aims to treat all parties humanely and with sensitivity, but without compromising the need for findings of criminal wrongdoing to be based on evidence and as the outcome of a fair legal process.